Equine maxillofacial intraosseous cystic lesions: a retrospective study of 17 cases - Kelley, Jennifer L.; Rawlinson, Jennifer E.; Bell, Cynthia M. (Frontiers in Veterinary Science, 2025)
IntroductionCystic and pseudocystic masses of the equine maxilla and mandible are rare lesions that result in clinically significant morbidity and/or mortality for the patient. Previous literature consists of case reports or case series. Few studies have addressed the variety of cystic lesions and comparative features. The aim of this study was to retrospectively describe the clinical signs, imaging findings, histopathologic diagnoses, treatments, and clinical outcomes for cystic masses in the equine maxilla and mandible.MethodsCases were recruited from six sources including a pathology laboratory, universities, and multiple private practices. Inclusion criteria were cystic/cavitated lesions within the maxilla mandible, and/or incisive bones that had a complete medical record that included history, gross appearance of the mass, diagnostic imaging, histopathology report, treatments performed, and clinical outcomes. Primary sinus cysts and teratomas were excluded from the study.ResultsLesions were identified in 17 patients with 1 patient having multifocal maxillomandibular cystic lesions. The most common lesion location was the body of the mandible. Diagnosis of lesion etiology and type was made by assimilating histopathology with clinical findings and imaging results. The following cysts were diagnosed: dentigerous cyst (6), bone cyst (6), and radicular cyst (3). Two lesions were unclassified, radiolucent inflammatory lesions. Patients were treated surgically with marginal excision and/or aggressive cyst lining debridement for 16/17 cases with rostral mandibulectomy performed in 1/17 cases. Excisional biopsies were performed at the time of definitive surgery for 12/17 cases, which resulted in histopathologic diagnoses. Follow-up ranged from 0 to 872 days postoperatively with a mean of 200 days with only 1 case having no follow-up. Eleven out of 17 cases (64.7%) had no documented recurrence following surgical excision. The overall complication rate was 35.3% (6/17 cases) and included orofacial/oroantral fistula formation, sinus flap suture reaction, and sinus flap mycosis.DiscussionDiagnosis and treatment of equine cystic masses of the maxilla, mandible, and/or incisive bones were greatly aided by assimilating oral exam and diagnostic imaging findings with histopathologic results.